Biodiesel Production from Chicken Fat Using - Felicia Felicia (Sriwijaya International Seminar on Energy-Environmental Science and Technology, 2014)
Biodiesel can be produced from either vegetable oil or animal fats through transesterfication process. Problem that usually appears in transesterification process is long reaction time because oil and alcohol are not mutually dissolved. The addition of co-solvent can help mixing the reactants. In this study chicken fat was used as feedstock for biodiesel production through transesterification reaction. The reaction of chicken fat using diethyl ether as co-solvent, NaOH as catalyst, and methanol as reactant at a ratio molar of methanol/ oil 6 : 1. Variables studied were temperature, reaction time, ratio of co-solvent to methanol, and the amount of catalyst on biodiesel characteristics. Products were analyzed by gas chromatography to obtain the composition of biodiesel. The biodiesel properties like methyl-ester content, density, and viscosity was evaluated and was found to compare well with Indonesian Standard (SNI). The results of this work showed that the use of chicken fat is very suitable as low cost feedstock for biodiesel production. The best result was obtained in a ratio of co-solvent/ methanol 0,5 : 1 (v/v), a temperature of 35oC, 20 minutes of reaction time, and 0,8 % (w/w) of catalyst amount.